Effects of the crisis on the occupational structure and work biography of immigrant population - Carrasco Carpio, Concepción; García-Serrano, Carlos (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2015)
This paper aims at examining in depth the occupational change and the work trajectories of individuals through time in order to provide a wider perspective of the effects of the 2008-2013 financial crisis on employment. We use microdata from the Labour Force Survey and carry out a comparison among three groups: the Spanish born in Spain, the Spanish born abroad and the non-Spanish born abroad. The results confirm that the latter group is characterized by the existence of a segmented occupational structure towards (highskilled and low-skilled) blue-collar jobs, a fact which has fostered a loss of employment in the work biography of the youngest cohorts of individuals during the recession.
Keywords: occupational change; work biography; immigrant workers